2012
DOI: 10.1212/wnl.0b013e31824367ab
|View full text |Cite
|
Sign up to set email alerts
|

Functional recovery after ischemic stroke—A matter of age

Abstract: Age emerged as a highly significant inverse predictor of good functional outcome after ischemic stroke independent of stroke severity, characteristics, and complications with the age-outcome association exhibiting a nonlinear scale and extending to young stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
153
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(165 citation statements)
references
References 32 publications
10
153
1
1
Order By: Relevance
“…It is generally in line with previous reports. 14,[18][19][20] However, our findings show that if the effectiveness of treatment is measured using a composite end point of mRS 0 to 2 or returning to prestroke mRS, the benefit in patients with prestroke mRS of 3 to 5 may match the benefit in patients with prestroke mRS of 2. During 3 months after thrombolysis, ≈1 in 3 patients from both groups returned to his/her previous mRS score.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It is generally in line with previous reports. 14,[18][19][20] However, our findings show that if the effectiveness of treatment is measured using a composite end point of mRS 0 to 2 or returning to prestroke mRS, the benefit in patients with prestroke mRS of 3 to 5 may match the benefit in patients with prestroke mRS of 2. During 3 months after thrombolysis, ≈1 in 3 patients from both groups returned to his/her previous mRS score.…”
Section: Discussionmentioning
confidence: 72%
“…19,20 Older age, stroke severity, and preadmission dependency additionally increase the risk of stroke-related pneumonia, which also strongly predicts poor outcome. 21 According to our data, 3-month mortality is higher with every level of prestroke disability, starting from 28% (preexisting mRS of 1) up to 48% (preexisting mRS of 3-5).…”
Section: Discussionmentioning
confidence: 99%
“…6,9,30 In our study, older age was associated with a poorer functional status in the medium term. As other investigators 27,31,32 have reported, age plays an important role in the functional recovery of patients, both at the time of discharge from the hospital and 6 months after a stroke, because scores on the Barthel Index decrease with age. This finding may indicate that older patients have poorer health status, which would affect their ability to recover and their degree of dependence.…”
Section: Discussionmentioning
confidence: 76%
“…The history of previous depression is a risk factor for the occurrence of post-stroke depression 7 . In addition, age is an inverse predictor of post-stroke functional independence 25 and lower functional dependence is related to PSD 7 . Thus, it is suggested that the elderly have a greater risk of developing depression after stroke.…”
Section: Discussionmentioning
confidence: 99%